Submission to the Ministry of Business, Innovation and Employment on the discussion document ‘work with engineered stone and materials containing crystalline silica' - Sissons, Jeff; Harper-Slade, Jon (New Zealand Journal of Health and Safety Practice, 2025)
This submission has been written by NZISM and CHASNZ with input from senior health and safety practitioners and occupational physicians. It outlines the background, discusses the problems with the status quo, and sets out our recommendations for change.